Factors Influencing Intrapartum Fatigue in Primigravida - Thaua, Wiphavanee; Phahuwatanakorn, Wanna; Pungbangkadee , Rudee (Nursing Science Journal of Thailand, 2024)
Purpose: This predictive research aimed to studying the influence of duration of labor, administration of oxytocin, anxiety, childbirth self-efficacy, and pain coping behaviors on intrapartum fatigue in primigravida. Design: Predictive correlational design. Methods: The samples consisted of 131 parturients admitted for delivery in the delivery room and postpartum ward at a super-tertiary care hospital in Bangkok. The instruments used for collecting data were a personal data form, the oxytocin administration record, Anxiety during Labor Questionnaire, the Thai Childbirth Self-efficacy Inventory, Pain Coping Behaviors Observation Form, and the Fatigue Questionnaire. Descriptive statistics, Pearson product moment correlation coefficient and multiple linear regression analysis were used to analyze data. Main findings: The result showed that 77.1% of subjects had low score of intrapartum fatigue. The mean intrapartum fatigue score was 52.78 points, which was categorized as low levels of fatigue. Duration of labor, administration of oxytocin, anxiety, childbirth self-efficacy, and pain coping behaviors could together explain 20.4% of the variance in intrapartum fatigue among primigravida (R2 = .20) with at least one factor could significantly predict intrapartum fatigue in primigravida (F = 6.42, p < .001). The predictors included anxiety and pain coping behaviors ( = .26, t = 2.75, p < .01; = - .26, t = -3.00, p < .01 respectively). Conclusion and recommendations: Anxiety and pain coping behaviors could predict intrapartum fatigue in primigravida. Therefore, it is suggested that midwives and nurses should reduce anxiety related to childbirth and promote efficient pain coping behaviors for preventing intrapartum fatigue.